(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To determine the prevalence of anxiety disorders and associated factors among HIV patients receiving treatment at Thu Duc City Hospital. Methods: A descriptive cross-sectional study was conducted on 369 HIV patients receiving treatment at Thu Duc City Hospital from March to May 2024. A convenient sampling technique, using a prepared questionnaire including the Generalized Anxiety Disorder-7 (GAD-7). The chi-square test (or Fisher’s exact test) and PR were used to determine associations. Results: The prevalence of anxiety disorders in HIV patients was 29,3%. Statistically significant factors related to anxiety disorders included the time since diagnosis, economic status and side effects. Conclusion: Mental health in HIV patients receiving treatment needs more attention, especially in groups with a short time since diagnosis, economic difficulties, and side effects.